2008
DOI: 10.5194/tc-2-191-2008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring uncertainty in glacier mass balance modelling with Monte Carlo simulation

Abstract: Abstract. By means of Monte Carlo simulations we calculated uncertainty in modelled cumulative mass balance over 400 days at one particular point on the tongue of Morteratsch Glacier, Switzerland, using a glacier energy balance model of intermediate complexity. Before uncertainty assessment, the model was tuned to observed mass balance for the investigated time period and its robustness was tested by comparing observed and modelled mass balance over 11 years, yielding very small deviations. Both systematic and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Furthermore, it has been frequently used in impact model applications (e.g. Corripio, 2002;Gruber, 2005;Machguth et al, 2008;Helbig et al, 2009) as well as other studies aiming at an optimal use of solar power, for example (Schillings, 2004). The Iqbal (1983) model assumes a homogeneous atmosphere and uses an isotropic view factor approach.…”
Section: S Gubler Et Al: Uncertainties Of Parameterized Surface Sdrmentioning
confidence: 99%
“…Furthermore, it has been frequently used in impact model applications (e.g. Corripio, 2002;Gruber, 2005;Machguth et al, 2008;Helbig et al, 2009) as well as other studies aiming at an optimal use of solar power, for example (Schillings, 2004). The Iqbal (1983) model assumes a homogeneous atmosphere and uses an isotropic view factor approach.…”
Section: S Gubler Et Al: Uncertainties Of Parameterized Surface Sdrmentioning
confidence: 99%
“…Similarly, intercomparison projects of runoff models by the World Meteorological Organization (e.g., WMO, 1986) revealed that simple models provided results comparable to more sophisticated models, given the difficulties of assigning proper model parameters and meteorological input data to each catchment element. Machguth et al (2008), analyzing model uncertainty with Monte Carlo simulations at one point on the tongue of Morteratsch Glacier in Switzerland, concluded that the output of well-calibrated models, when applied to extrapolate in time and space, is subject to considerable uncertainties due to the quality of input data. According to Carturan et al (2012a), who compared three melt algorithms in a 6-year application of an enhanced temperature-index model over two Italian glaciers, uncertainties in extrapolating temperature measurements from off-site data partly mask the peculiar behavior of each algorithm and do not allow definitive conclusions to be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g., Gurgiser et al, 2013;Machguth et al, 2008). In order to minimize respective uncertainties in the mass balance model, we made recourse of a calibration procedure which integrates available snow information.…”
Section: Model Tuning For Individual Stakes and Yearsmentioning
confidence: 99%
“…This stake was chosen as the relatively homogeneous surrounding makes it representative for a wider region of the glacier and it offers by far the highest number of stake readings in the upper region of Langenferner. It is hence the best choice for the optimization of model parameters, which was done applying a Monte Carlo approach (e.g., Machguth et al, 2008;Mölg et al, 2012) performing 1000 model runs with different parameter combinations in order to find the best model setting for the local conditions. The optimal parameter combination was then applied to all stake locations in the upper glacier part.…”
Section: Monte Carlo Optimization Of Model Parametersmentioning
confidence: 99%